Estratégias discursivas no Programa Profissão Repórter: os sentidos de cidadania aquém e além do discurso - Conrad, Kalliandra Quevedo (2018)
Based on the assumption that the media are a field aimed at producing forms of making individuals’ citizenship into discourse, we perceive that the notions of citizenship are generally associated to the electoral period, more specifically with the exercise of a political right: the vote. We understand, however, that the idea of citizenship goes far beyond this narrow perspective, since we see it as a concept capable of encompassing meanings constructed over time, as well as of rebuilding them in each new historical epoch. Therefore, this thesis is about citizenship, discourse and production of meanings in television media, here delimited to the study of the discursive strategies of the television program Profissão Repórter (“Profession: Reporter”) by Globo Network. The research problem that underlies this research focuses on the following question: which meanings of citizenship are produced by the discursive strategies of the aforementioned TV program? Our objectives are: to formulate a conceptual framework for the comprehension of citizenship in order to make a theoretical-methodological matrix for the analysis of the discursive strategies of Profissão Repórter; to bring theoretically together the concept of citizenship and the discursive-mediatic perspective, taking the empirical object as a citizenship-related issue; and to systematize the core meanings of citizenship produced by Profissão Repórter’s discursive strategies. Emphasizing the (re)production of inequality in social practices, we use the theoretical-methodological approach of Critical Discourse Analysis (CDA), based on the studies of Norman Fairclough (2016). The analytic corpus was drawn using a thematic clipping, in which we selected five episodes that dealt with the right to education. Each program was analyzed using the analytical categories of vocabulary, textual structure and manifest intertextuality. Regarding the findings, we identified ten sets of meanings that brought together different ways of signifying citizenship (including their silencing) from the subject positions mapped in the discourse. These sets are: citizenship as scarcity, citizenship as examination, citizenship as dramatization, citizenship as delegitimization, citizenship as authoritarianism, citizenship as protagonism, citizenship as resistance, citizenship as privilege, citizenship as transformation, and citizenship as democracy. We understand the latter as the key meaning that should guide citizenship practices in media discourses. Based on these sets of meanings, we point to the coexistence of two main categories in the intentionalities of the TV program: a pasteurized media-discursive citizenship and a democratic media-discursive citizenship.